THE EFFECTS OF TRADITIONAL GAME ‘CONGKLAK’ AND SELF-CONFIDENCE TOWARDS LOGICAL MATHEMATICAL INTELLIGENCE OF 5-6 YEARS CHILDREN - Anik Lestariningrum (Universitas Muhammadiyah Ponorogo, 2018)
The purpose of this study was to determine the influence of traditional games ‘congklak’ and self-confidence towards mathematical logical intelligence. Mathematical logical intelligence concept proposed by Howard Garnder becomes the foundation of the emergence of the young learners teaching learning process that considers young learners individual potential. Playing is one of the ways for the young learners to learn and traditional game is one of the ways to develop the mathematical logical intelligence. By applying the suitable traditional game, both the students’ self-confidence and the mathematical logical intelligence can be improved. In order to know the effect of traditional games and self-confidence to the mathematical logical intelligence, the experimental research using ANAVA analysis was applied. It was found that traditional game “congklak” with the high level of self- confidence students was better than those with the low self- confidence students. The result of the data analysis also showed that there was interactional effect between traditional game and self -confidence to the mathematical logical intelligence in which F observed =114,023 was bigger than l F table = 3,95 in the level of significance α 0.05.